Library Borrowing System for SK Jelotong by Using QR Code - Madzidon, Aida Husna; Nur Ziadah Harun (Applied Information Technology And Computer Science, 2022)
Generally, every library borrowing system has same the main goal which is to gather, store, organize, access and provide information to users. The library is commonly used in educational institutions. School libraries are important for the students but the library in SK Jelotong still uses the manual system of borrowing books which is outdated and not secured. The proposed library borrowing system will be developed in the QR code approach. It will introduce authentication through username and password. It will be used by the librarians and administrators. This project is using the Waterfall model in a way to complete the findings and the language used are PHP, HTML, CSS, and MySQL. This project is designed to make borrowing books easier for students. Besides, it also helps the administrator in tracking the record. The book data can be fetched in one go by scanning the book QR code. By developing this system, it will replace the traditional way of borrowing method which is the record was hand-written and kept in a book. Lastly, a few security approaches are implemented to the system such as password hashing and login credentials, so it will secure the system user from the data breach of the physical record.